Filozofia w działaniu czyli przemiany gospodarczo-społeczne w Barbaricum w późnym okresie wpływów rzymskich i u progu wędrówek ludów - Gralak, Tomasz (Folia Praehistorica Posnaniensia, 2025)
The economy of the European Barbaricum was a dynamic system – variable in time and differentiated in terms of territory. In Central Europe’s Early Roman Iron Age, a segmental society with an autarkic economy is visible. It is characterized by dispersed power, dispersed capital, and dispersed production. The primary means of production – arable land – were collectively owned. The factor that stimulated the changes was Roman influences. Another was limitations on agricultural production, leading to the Malthusian crises. With unfavorable climatic changes (cooling down), this led to a radical reorganization of agriculture. This was a reason for the creation of a strongly hierarchical community and the centralization of production. The consequence was also the concentration of power and capital.